2020
DOI: 10.1016/j.ijso.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Preventive strategies of residual neuromuscular blockade in resource-limited settings: Systematic review and guideline

Abstract: Background: Following surgery, neuromuscular paralysis is no longer needed, its action could be quickly and effectively terminated. However, evidences shown that NMBAs often continues in the PACU, even after the administration of acetylcholinesterase inhibitor. Hence, stratifying risks of patients and developing evidence-based guidelines are required by rationalizing residual neuromuscular block preventive strategies in resource limiting setup. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…16 Studies from Singapore and UK have shown that only 10%-13% of anaesthetists routinely use objective neuromuscular monitoring despite its availability because of additional efforts required. 4 A 2017 consensus statement by an international panel of experts recommended that quantitative (objective) NMB monitoring should be used whenever nondepolarizing NMBs are administered. Until conventional nerve stimulation devices are replaced with quantitative monitoring equipment, use of nerve stimulation monitoring should be mandatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Studies from Singapore and UK have shown that only 10%-13% of anaesthetists routinely use objective neuromuscular monitoring despite its availability because of additional efforts required. 4 A 2017 consensus statement by an international panel of experts recommended that quantitative (objective) NMB monitoring should be used whenever nondepolarizing NMBs are administered. Until conventional nerve stimulation devices are replaced with quantitative monitoring equipment, use of nerve stimulation monitoring should be mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nevertheless, residual neuromuscular block is preventable by adequate monitoring of the patient and timing the reversal and extubation procedures. 4 This survey aimed to understand the use of NMBs among Indian anaesthesiologists, including their choice and dosages of NMBs, neuromuscular monitoring, use of reversal agents for residual neuromuscular block, and incidence of adverse effects. https://doi.org/10.18231/j.ijca.2023.053 2394-4781/© 2023 Author(s), Published by Innovative Publication.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of hypothermia and use of a nerve stimulator to assess the degree of the block during the procedure and to detect residual paralysis during recovery from anaesthesia are recommended. 27 Using the smallest dose of an NMB and avoiding the use of long-acting NMBs can prevent residual paralysis. 18 The transplant anaesthesia experts who were in this panel also prefer cisatracurium or atracurium as the NMB of choice for FTA.…”
Section: Role Of Neuromuscular Blockers In Fta and Reversal Agents Usedmentioning
confidence: 99%
“…The phenomenon of residual neuromuscular block is more common in elderly, female, and hypothermic patients. 11 Fortunately, this can be avoided by the appropriate assessment of a patient and by carefully monitoring the degree of muscle relaxation. 6 Assessment of muscle function on the basis of clinical tests, despite its long history of use, is today considered a very unreliable method and should not be applied in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of residual neuromuscular block is more common in elderly, female, and hypothermic patients. 11 Fortunately, this can be avoided by the appropriate assessment of a patient and by carefully monitoring the degree of muscle relaxation. 6…”
Section: Introductionmentioning
confidence: 99%